2018
DOI: 10.1007/s11356-018-1904-7
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Lu(III) sorbed on 2-line ferrihydrite at pH 5.7 and aged for 12 years at room temperature. II: insights from STEM-EDXS and DFT calculations

Abstract: Transformation products of two-line ferrihydrite associated with Lu(III) were studied after 12 years of aging using aberration-corrected high-angle annular dark field scanning transmission electron microscopy (HAADF-STEM), high-efficiency energy-dispersive X-ray spectroscopy (EDXS), and density functional theory (DFT). The transformation products consisted of hematite nanoparticles with overgrown goethite needles. High-efficiency STEM-EDXS revealed that Lu is only associated with goethite needles, and atomic-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 59 publications
(1 reference statement)
1
5
0
Order By: Relevance
“…In sample T2, particles have sizes of about 100-200 nm and in T2 super needles have about 10-30 nm in diameter and < 500 nm in length. These values are consistent with those obtained by transmission electron microscopy (Yokosawa et al 2018).…”
Section: Morphology Mineralogical and Elemental Compositionssupporting
confidence: 92%
See 1 more Smart Citation
“…In sample T2, particles have sizes of about 100-200 nm and in T2 super needles have about 10-30 nm in diameter and < 500 nm in length. These values are consistent with those obtained by transmission electron microscopy (Yokosawa et al 2018).…”
Section: Morphology Mineralogical and Elemental Compositionssupporting
confidence: 92%
“…Information on the retention mode and on the nature of the host phase was obtained by X-ray absorption spectroscopy at the Lu L 3 -edge. Complementary STEM-HAADF investigations on the same sample and DFT calculations will be presented in an companion paper (Yokosawa et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Sun et al carried out DFT calculations using different cluster models for the brucite layer. Our theoretical approach to investigate radionuclide interaction with GR is a continuation of previous theoretical attempts on similar systems (see, for example, refs and ).…”
Section: Introductionmentioning
confidence: 99%
“…Along with phase transformation, various metal ions are often associated with ferrihydrite, leading to the variation of stability and mobility of metals in terrestrial environments. Aging studies of ferrihydrite with metals (e.g., Cd­(II), Mn­(II), Ni­(II), and Pb­(II)) showed that the transformation reactions were influenced by the structural incorporation of metals into recrystallized oxides. , A few studies showed that the phase transformation of ferrihydrite was also affected by adsorbed REEs (e.g., Lu­(III)). , However, the mechanisms responsible for the suppressed ferrihydrite transformation by REEs are not clearly understood.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 A few studies showed that the phase transformation of ferrihydrite was also affected by adsorbed REEs (e.g., Lu(III)). 27,28 However, the mechanisms responsible for the suppressed ferrihydrite transformation by REEs are not clearly understood.…”
Section: ■ Introductionmentioning
confidence: 99%